(untitled) (Texas Journal of Medical Science, 2024)
The article presents data on the structure of morbidity and features of the modern course of respiratory diseases in children of Andijan. The relevance, place among bronchopulmonary diseases, and features of the course of modern bronchitis in childhood are determined. A brief clinical description is given and the main approaches to the treatment of acute bronchitis are identified. Data from clinical experience with the use of the non-steroidal anti-inflammatory drug fenspiride hydrochloride (Erespal) in children are presented. High anti-inflammatory, bronchodilator, indirect mucoactive and antitussive effects of the drug in the complex treatment of bronchitis in children were noted